The study of measurement and determination of water retention characteristics of coal ash - Mathoho, Gundo (My University, 2021)
Eskom produces million tons of ash from burning coal for power generation. The majority of the generated coal ash generated ends up in designated dry ash dumps. This study assessed various physical and geochemical properties of coal ash to estimate the water retention of a dry coal ash dump. Also, coal ash geochemical properties were studied to ascertain its leachability and identify possible mineralogical phases responsible for water retention. It is a national priority to improve water conservation, quality, and water usages to avoid water demand exceeding currently limited available supplies. South Africa is a water-scarce country. Groundwater resources play a vital role in ensuring sustainable water security for the country in both rural and urban areas. Groundwater pollution from the dry ash disposal facilities also referred to as ash dumps remains a threat to the precious water resource. Generally, the leachate associated with heavy metal toxins and other inorganic contaminants is of concern and may cause detrimental health effects as well as environmental damage. Pollution of groundwater pollution may occur from the ash dumps particularly when the field capacity is exceeded. This study through construction and assessment of various water characteristic curves estimated the field capacity of an ash dump. Sieving together with the hydrometer analysis were conducted to determine the coal ash particle sizes and distribution. The texture of Matimba coal ash is silt-loam and can be generally characterised as fines. Fine-grained materials generally exhibit better water retention properties than coarse-grained materials due to the high surface area available for possible ADForption of water molecules. However, the results also indicate ash with an insignificant amount of clay particles (<0.002 mm) but rather dominated by silt-sized particles (0.05-0.002 mm). QEMSCAN, a scanning electron microscope was used to analyse the bulk mineral composition of the coal ash samples. The mineralogical composition of coal ash characteristically resembles the composition of the original parent coal, which is generally dominated by the high proportion of aluminosilicate, quartz, and glass cenospheres. The mineralogical analysis on both samples yielded appreciable quantities of clay mineral, with Kaolinite as the dominant mineral phase. TCLP tests were conducted to determine the leachability of the ash. Trace elements are chemical elements present in ash in small amounts, but still at lower levels pose a threat to the environment and human health. The detected trace elements from TLCP results in an increasing concentration order are Manganese>Chromium>Copper. HYPROP-FIT software was used to access and analyse the ash retention experimental data recorded and acquired using HYPROP-View software. The tested ash material suggests a high moisture retention capacity at low suction, with a progressive decrease in retention apparent with increasing negative head pressures. The study found the Brooks-Corey model as a suitable representative of the Hyprop measured data, confirmed by AICc and RMSE analysis. The Brooks-Corey estimated retention function parameters within +/-1% error. A mean value of 35.3% for the three samples was determined as the water retention or field capacity value for Matimba Coal ash. After considering site-specific conditions like rainfall and evaporation rate within Matimba ash disposal facility, the active ashing portion can hold about 7.96 megalitres per day of liquid through its capillary storage. If the ash dump is operated in excess of this value, the chances of groundwater pollution are high. It is essential to treat this value as an overestimate, and be used to aid in terms of realistically determining dust suppression or irrigation volumes, for overall effective water management at a dry coal ash dump
A research report submitted in partial fulfillment of the requirements for the degree Master of Science in Chemical Engineering (50/50), in the Faculty of Engineering and Built Environment (School of Chemical and Metallurgical Engineering) at the University of the Witwatersrand, 2021